Pengaruh Operating Capacity, Likuiditas, Profitabilitas Dan Solvabilitas Terhadap Financial Distress Pada Perusahaan Subsektor Hotel, Restoran Dan Pariwisata Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2023 - Putri, Meyleni; Armin, Rini; Dwihandoko, Toto Heru (PT. Kreasi Karya Majakata, 2024)
Hotel, Restaurant and Tourism Subsector companies that have negative earning per share values for 2 consecutive years. This indicates that the company is experiencing financial distress or financial difficulties. financial distress occurs due to the company's inability to manage and maintain financial performance, resulting in the company experiencing operational losses. This study aims to test and analyze the effect of operating capacity, liquidity, profitability and solvency on financial distress in Hotel, Restaurant and Tourism Subsector Companies listed on the Indonesia Stock Exchange for the 2020-2023 Period. This study uses a type of quantitative research. Sampling using purposive sampling technique, obtained 8 companies with 4 years of research. The analysis used in this research is multiple linear regression analysis. The results showed that, operating capacity affects financial distress, liquidity has no effect on financial distress, profitability affects financial distress, and solvency affects financial distress.